New economy, new agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
This first year of the new millennium is full of excited talk about the 'New Economy', with its new approaches to fame and fortune, if not happiness. But that isn't all that s on the move: isn't it also time for a 'New Agriculture'? Maybe you have...